원목 및 톱밥배지 버섯 재배사 내 실내 공기서 분리한 미기록 진균 보고 - 안금란; Geum Ran Ahn; 김지은; Ji Eun Kim; 김준영; Jun Young Kim; 김성환; Seong Hwan Kim (Hangug gynnhaghoi ji, 2018)
Oak mushroom is cultivated using logs and sawdust media as substrates. In this study, fungi were isolated during a monitoring of indoor air in the oak mushroom cultivation houses located in Cheongyang-gun of Chungnam, Geoje-gun of Gyeongnam, Gumi-si of Gyeongbuk, Jangheung-gun of Jeonnam and Yeoju-si of Gyeongggi-do. Identification of the fungi based on morphology and molecular analysis of the internal transcribed spacer region and 28S rDNA, translation elongation factor translation elongation factor 1 a gene, and β-tubulin gene revealed that six fungi, Cenangium acuum, Neopestalotiopsis surinamensis, Metarhizium marquandii, Periconia macrospinosa, Trichoderma petersenii, and Trichoderma paratroviride that have not been recorded previously in Korea.